Association of platelet activation markers with recurrence of atrial fibrillation after pulmonary vein isolation. (19th May 2017) - Pfluecke, Christian; Plichta, Lina; Tarnowski, Daniel; Forkmann, Mathias; Ulbrich, Stefan; Quick, Silvio; Heidrich, Felix M.; Wiedemann, Stephan; Christoph, Marian; Poitz, David M.; Wunderlich, Carsten; Strasser, Ruth H.; et al.
Abstract: Atrial fibrillation (AF) is known to cause platelet activation. AF and its degree of thrombogenesis could be associated with monocyte-platelet aggregates (MPAs). We investigated on whether the content of MPAs or other platelet activation markers is associated with the recurrence of AF after pulmonary vein isolation (PVI). A total of 73 patients with symptomatic AF underwent PVI. After 6 months, all patients were evaluated for episodes of AF recurrence. At the same time, flow-cytometric quantification analyses were performed to determine the content of MPAs. Further platelet activation parameters were detected by using either cytometric bead arrays or quantitative immunological determination. Patients with recurrent AF ( n = 20) compared to individuals without AF relapse ( n = 53) were associated with an increased content of MPAs (43 ± 3% vs. 33 ± 2%, p = 0.004), as well as an increased CD41 expression on monocytes (191 ± 20 vs. 113 ± 6, p = 0.001). The level of the soluble platelet activation markers such as D-dimer, sCD40L, and sP-selectin did not differ between these groups. The content of MPAs correlated weakly with the level of sCD40L ( r = 0.26, p = 0.03), but not with sP-selectin and D-dimer, whereas sP-selectin and sCD40L correlated with each other ( r = 0.38, p = 0.001). Only the cellular marker of platelet activation, the content of MPAs, was increased in patients with recurrent AF after PVI. In contrast, soluble markers remained unaltered. These data indicate a distinct mechanism and level of platelet activation in AF. The clinical relevance of MPAs in identifying AF recurrence or in guiding the therapy with anticoagulants remains to be elucidated.